HEALTH PROMOTION: PERSPECTIVE OF NURSING STUDENTS FROM A HIGHER EDUCATION INSTITUTION IN PARAÍBA (Fiep Bulletin - online, 2013)
Objective: to identify the knowledge of nursing students from a higher education institution in the backlands of Paraiba about health promotion (HP). Methodology: an exploratory, descriptive qualitative approach to data collection being carried out with the graduating students from the Nursing Course at the Santa Maria College. Results: pointed out that subjects understand the HP as being part of the activities developed by health professionals in search of quality of life for individuals, in which the Health Education is one of the most important, because it brings with it an approximation of the professionals with the community, by raising awareness through lectures, campaigns and other means; immunization and knowledge about health problems and their causative agents, with a focus on self-care. Conclusion: even before the knowledge learned there needs to be more interaction between the theoretical and practical knowledge of nursing, and from there providing effective, efficient and conscious HP, even more so being offered to the population.
Keywords: Primary Health Care; Health Promotion; Nursing.